COMPARISON OF SCIENCE LEARNING RESULTS USED E-LEARNING AND ZOOM APPLICATIONS IN DISTANCE LEARNING AT SMP N 9 AMBON - Tehupary, Eifan Chrismis; Matdoan, Muh Nur (RUMPHIUS, 2022)
The development of information and communication technology at this time is very rapid. This can be seen from the increasingly sophisticated communication and information tools such as mobile phones and computers. Mobile phones that used to only feature telephones, now they are very developed to the point of 4G technology that can speed up the flow of delivery. In help students in the learning process of SMP N 9 AMBON, they use 2 applications, namely the E-Learning application and the Zoom application. This study uses quantitative and qualitative descriptive analysis techniques. Data about the observations were analyzed qualitatively. Student learning outcomes data were analyzed quantitatively by calculating the average score, standard deviation, median, highest score, and lowest score, this study also used inferential analysis techniques used to test research hypotheses. Based on the results of research and data analysis, for students who were given the treatment of learning models using the Zoom application, the results obtained were the average value of 47.5 out of a maximum score of 100. Based on the results of research and data analysis, for students who were given the treatment of learning models using the E-Learning application, the results obtained were the average value of 45.71 from a maximum score of 100.